Mild Propofol Sedation Reduces Frontal Lobe and Thalamic Cerebral Blood Flow: An Arterial Spin Labeling Study - Saxena, Neeraj; Gili, Tommaso; Diukova, Ana; Huckle, Danielle; Hall, Judith E.; Wise, Richard G. (Frontiers in Physiology, 2019)
Mechanisms of anaesthetic drug-induced sedation and unconsciousness are still incompletely understood. Functional neuroimaging modalities provide a window to study brain function changes during anaesthesia allowing us to explore the sequence of neuro-physiological changes associated with anaesthesia. Cerebral perfusion change under an assumption of intact neurovascular coupling is an indicator of change in large-scale neural activity. In this experiment, we have investigated resting state cerebral blood flow (CBF) changes in the human brain during mild sedation, with propofol. Arterial spin labelling (ASL) provides a non-invasive, reliable and robust means of measuring cerebral blood flow (CBF) and can therefore be used to investigate central drug effects. Mild propofol sedation related CBF changes were studied at rest (n=15), in a 3T MR scanner using a PICORE-QUIPSS II ASL technique. CBF was reduced in bilateral paracingulate cortex, premotor cortex, Broca’s areas, right superior frontal gyrus and also the thalamus. This cerebral perfusion study demonstrates that propofol induces suppression of key cortical (frontal lobe) and subcortical (thalamus) regions during mild sedation.